Solutions of the Polchinski ERG equation in the O(N) scalar model - Kubyshin, Yuri (2017)
Solutions of the Polchinski exact renormalization group equation in the scalar O(N) theory are studied. Families of regular solutions are found and their relation with fixed points of the theory is established. Special attention is devoted to the limit $N=∞$, where many properties can be analyzed analytically.